(untitled) (Bangladesh Journal of Nuclear Agriculture, 2025)
Organic matter amendments significantly improve soil fertility and increase rice yields. The study was conducted to investigate the effects of integrating organic amendments with chemical fertilizers on soil fertility and yields of T. aman and Boro rice. Field experiments were conducted, employing five treatments: T1: Native soil fertility (Control), T2: 100% chemical fertilizers (100% CF), T3: CF+2.5 t ha-1 rice straw (CF+RS, Integrated Plant Nutrient System (IPNS)), T4: CF+4 t ha-1 cowdung (CF+CD (IPNS)), T5: CF+3 t ha-1 poultry manure (CF+PM (IPNS)). The results indicated that integrating organic amendments with reduced rate of chemical fertilizers significantly improved rice yield and soil fertility compared to the only application of chemical fertilizers. The treatment T4, incorporating cowdung with chemical fertilizers exhibited the highest grain yield, surpassing even the 100% chemical fertilizer treatment. This superior performance may be attributed to the soil fertility parameters, including increased organic matter content and nutrient availability (N, P, K, S). Furthermore, all the treatments of organic amendments demonstrated comparatively higher yields than the 100% chemical fertilizer alone, suggesting a viable strategy for reducing reliance on chemical fertilizers and promoting sustainable rice production. This study underscores the crucial role of organic matter in maintaining soil health and productivity, advocating for the adoption of integrated nutrient management practices to ensure both agricultural sustainability and environmental protection in Bangladesh. Bangladesh J. Nuclear Agric, 39(2): 87-96, 2025